Access on Demand on Wi-Fi Networks: the Impact of Dynamic Switching of Providers for the Mobile User - Augusto, Mario E.; Moreira, Edson S. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance), 2012)
With the access on demand the mobile device manages the handovers and might not need to have a service contract for connecting to a network. These features may improve or worsen the user access experience and cause some impacts related to, for instance, the received throughput, paid price and number of handovers. This paper presents the performance evaluation results of an access on demand environment with Wi-Fi networks compared to the traditional access (not on demand), through simulation. It also shows how the application, the speed of the mobile and the traffic of other users can influence the number of handovers, paid price and the total of received bytes by a mobile. The mobile device can prioritize price, received signal strength or load on the access point.